2008
DOI: 10.1111/j.1462-5822.2008.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Capsular polysaccharides galactoxylomannan and glucuronoxylomannan from Cryptococcus neoformans induce macrophage apoptosis mediated by Fas ligand

Abstract: SummaryThe effects of capsular polysaccharides, galactoxylomannan (GalXM) and glucuronoxylomannan (GXM), from acapsular (GXM negative) and encapsulate strains of Cryptococcus neoformans were investigated in RAW 264.7 and peritoneal macrophages. Here, we demonstrate that GalXM and GXM induced different cytokines profiles in RAW 264.7 macrophages. GalXM induced production of TNF-a, NO and iNOS expression, while GXM predominantly induced TGF-b secretion. Both GalXM and GXM induced early morphological changes iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
128
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(139 citation statements)
references
References 36 publications
7
128
3
1
Order By: Relevance
“…Mouse Th17 differentiation occurs only in the simultaneous presence of IL-6 and TGF-␤, while IL-23 represents a growth factor rather than a differentiation factor (8). It has been previously reported that GXM is able to induce TGF-␤ in macrophages (49). In our experimental system GXM suppresses TGF-␤ in joints early after the onset of treatment.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Mouse Th17 differentiation occurs only in the simultaneous presence of IL-6 and TGF-␤, while IL-23 represents a growth factor rather than a differentiation factor (8). It has been previously reported that GXM is able to induce TGF-␤ in macrophages (49). In our experimental system GXM suppresses TGF-␤ in joints early after the onset of treatment.…”
Section: Discussionmentioning
confidence: 63%
“…This apparent discrepancy could be due to the different experimental systems used. In particular in a report from Villena et al (49) the regulation of GXM was evidenced in an in vitro system by using a macrophage cell line. This experimental condition is quite different from that used by us.…”
Section: Discussionmentioning
confidence: 99%
“…72) and also for fungal pathogens such as Cr. neoformans (24). However, we did not observe signs of apoptosis by C. glabratainfected MDMs, indicating that, at least during the early stages (24 h) of interaction, C. glabrata does not induce apoptosis.…”
Section: Escape From Macrophagesmentioning
confidence: 55%
“…Additionally, C. albicans modulates the immune response indirectly via manipulating the host's cytokine response (22,23). The capsule of Cryptococcus neoformans has been shown to mediate macrophage apoptosis and therefore induces a distinct anti-inflammatory mechanism to kill the phagocyte (24). Cr.…”
mentioning
confidence: 99%
“…GXM is the more abundant capsule component; cells without it are acapsular and are avirulent in animal models of cryptococcal infection (28). GXMGal comprises less of the capsule mass but also exhibits potent immunomodulatory properties (32)(33)(34)(35)(36) and may regulate capsule expansion (37).…”
mentioning
confidence: 99%